ANESTHESIA PECULIARITIES IN BEACH CHAIR POSITION (LITERATURE REVIEW) - Lyzohub, Mykola; Lyzohub, Kseniia; Kotulskiy, Igor; Pazdnikov, Roman; Kostrikova, Eleonora; Yakovenko Svіtlana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Beach chair position (BCP) that is applied for shoulder surgery has a number of advantages for surgeons, but it may lead to intraoperative hypotension, bradycardia and postoperative neurologic complications. Objective of the publication is to review up-to-date literature to emphasize complications related to BCP and methods of their monitoring and prophylaxis. Methods. We have analyzed publications from Google Scholar, PubMed, and specialized scientific journals databases. Results. In orthopedic practice the main types of surgical positions that are used for shoulder surgery are the next: semi-BCP — 30°, BCP — 60°, Semi-upright sitting position — 90°. In spite of its correlations with hemodynamic changes the tilt angle is rarely measured in clinical practice. The etiology of nervous system impairment is thought to be hypotension and subsequent brain hypoperfusion that is induced by BCP under general anesthesia. Blood pressure at the standard brachial level is significantly higher than at the meatus acoustic level. That is why today the safety level of blood pressure for BCP surgery is not clearly estimated. The majority of clinical investigations have shown that BCP leads to decreasing of regional cerebral blood flow and brain oxygenation. The high incidence of cerebral desaturation events in BCP (more than 50 %) require its accurate monitoring. The most widely used method is NIRS (near-infrared spectroscopy). Other methods including Doppler scanning of brain vessels and jugular saturation has limited clinical using. In majority of trials of cerebral desaturation events has shown to have controversial impact on postoperative cognitive dysfunction. Serum neurospecific proteins examination may be a perspective method of further investigations for neurologic impairment after surgeries in BCP.